2023
DOI: 10.3390/ijerph20032586
|View full text |Cite
|
Sign up to set email alerts
|

News of the Pedagogical Models in Physical Education—A Quick Review

Abstract: In the last two decades, research has proliferated in the field of pedagogical models used in school Physical Education. The growth is so high that it is necessary to do a quick review to know which models currently exist and which are emerging. The objective of this work is to collect all the models or pedagogical approaches present in the scientific literature related to school Physical Education and to make known, to the scientific and academic community, its main purposes and characteristics. A quick revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 127 publications
1
10
0
1
Order By: Relevance
“…The authors also confirm that these components are specific parts of the professional training of physical education teachers. Such thoughts are also reflected in the scientific research of other authors (Arufe-Giráldez et al 2023;Casey & Kirk, 2020). In particular, previous studies have confirmed that the activities of physical education teachers must first be organized on the basis of general laws and principles of education and must strictly obey these requirements (e.g., Enright e .al., 2017;Fernandez-Balbora, 1997).…”
Section: Physical Education Teacher In Middle Schools: Requirements …mentioning
confidence: 81%
“…The authors also confirm that these components are specific parts of the professional training of physical education teachers. Such thoughts are also reflected in the scientific research of other authors (Arufe-Giráldez et al 2023;Casey & Kirk, 2020). In particular, previous studies have confirmed that the activities of physical education teachers must first be organized on the basis of general laws and principles of education and must strictly obey these requirements (e.g., Enright e .al., 2017;Fernandez-Balbora, 1997).…”
Section: Physical Education Teacher In Middle Schools: Requirements …mentioning
confidence: 81%
“…The t-value of physical skills index was -0.062 (p > 0.05), indicating that there was no significant difference between the physical skills of students in the experimental class and the control class after the experiment, i.e., the effect of the competitive education model on students' physical skills was not significantly different from that of the traditional teaching method. Skill learning is a gradual and long-term practice process, and although students in the experimental class had many learning advantages over students in the control class during one experimental cycle, the advantages of the competitive education model could not be reflected in skill learning due to the limitations of the researcher's time and other limitations [13][14].…”
Section: Resultsmentioning
confidence: 99%
“…By harnessing the power of technology, educators can create dynamic, interactive learning environments that transcend the constraints of traditional classroom settings, catering to the diverse needs and preferences of today's digital-native learners. Additionally, the flipped classroom model lends itself to the implementation of inquiry-based learning approaches, wherein students are encouraged to explore, question, and construct meaning through hands-on, experiential learning activities [4]. By capitalizing on class time for collaborative problem-solving, group discussions, and project-based learning initiatives, educators can foster critical thinking skills, creativity, and collaboration among students, preparing them to navigate the complex challenges and uncertainties inherent in sports contexts.…”
Section: Flipped Classroom Modelmentioning
confidence: 99%